Molecular Regulators of Metabolism and Cardiometabolic Disease - Indriyanti Rafi Sukmawati; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2012)
BACKGROUND: The mechanisms that are responsible for energy management in cells in an organism require a complex network of transcription of factors and cofactors.CONTENT: All living system must maintain a tight equilibrium between energy intake, storage and expenditure for optimal performance. This tight equilibrium must be both robust and flexible to allow for adaptation to every situation such as exercise or rest and famine or feast. Organisms rely on finely tuned and complex signaling network to confront with all possibilities. Metabolic imbalance can cause dysfunction and pertubation of these networks, which if uncorrected will induce disease such as obesity and diabetes mellitus.SUMMARY: During the last decades the understanding of the transcriptional regulation of diverse metabolic pathways has contributed to the elucidation of mechanisms of metabolic control and to a better knowledge of the pathogenesis of metabolic diseases. KEYWORDS: AMPK, SIRT1, PGC-1α, FGF21, mTORC1